Fleksibilitas Ibadah bagi Pekerja Modern: Analisis Kaidah Idzā Ḍāqa al-Amru Ittasa‘a dalam Konteks Dunia Kerja Kontemporer - Muhammad Nurtaufiq Sudirman; Tarekh Surya Anugrah; Sepmin Alfurqan; Achmad Musyahid Idrus; Muammar Bakry (Lembaga Yasin AlSys, 2026)
The worship-related problems of modern workers indicate the need for an understanding of fiqh that is flexible, proportional, and still grounded in sharia provisions, especially when work demands create limitations in time, place, and physical condition in performing worship. This study aims to examine the concept of the maxim idzā ḍāqa al-amru ittasa‘a as a principle of flexibility in Islamic law, analyze the limits of its application in fiqh, and explain its implementation in the worship-related problems of modern workers. This study used a qualitative approach with a library research design through an examination of classical and contemporary fiqh literature and an analysis of various cases involving modern workers. The results show that this maxim provides legitimacy for various forms of rukhsah in worship that are relevant to the conditions of modern workers, such as the permissibility of combining prayers for medical personnel in emergency conditions, transportation workers with high mobility, rescue teams in disaster situations, and concessions in purification through tayamum when adequate facilities are unavailable. Under certain conditions, this maxim also allows adjustments in the performance of worship due to time and place constraints, such as for workers in dense work environments or in situations of extreme traffic congestion, while still observing sharia limits. However, the application of rukhsah is not absolute because it must be adjusted to the provisions and conditions formulated by scholars. The conclusion of this study affirms that Islamic law has a flexible yet measured character in providing ease for mukallaf according to the level of difficulty faced in modern life. The implications of this study contribute to the development of contemporary fiqh studies, particularly in formulating Islamic legal responses that are adaptive to the dynamics of modern work without disregarding the principles of prudence and sharia compliance.